The N-terminus of the serum- and glucocorticoid-inducible kinase Sgk1 specifies mitochondrial localization and rapid turnover - Engelsberg, Arne (Portland Press Ltd., 2006)
The serine/threonine protein kinase Sgk1 (serum- and glucocorticoid-inducible kinase 1) is characterized by a short half-life and has been implicated in the control of a large variety of functions in different subcellular compartments and tissues. Here, we analysed the influence of the N-terminus of Sgk1 on protein turnover and subcellular localization. Using green fluorescent protein-tagged Sgk1 deletion variants, we identified amino acids 17–32 to function as an anchor for the OMM (outer mitochondrial membrane). Subcellular fractionation of mouse tissue revealed a predominant localization of Sgk1 to the mitochondrial fraction. A cytosolic orientation of the kinase at the OMM was determined by in vitro import of Sgk1 and protease protection assays. Pulse–chase experiments showed that half-life and subcellular localization of Sgk1 are inseparable and determined by identical amino acids. Our results provide evidence that Sgk1 is primarily localized to the OMM and shed new light on the role of Sgk1 in the control of cellular function.